2023
DOI: 10.1097/aci.0000000000000933
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of anaphylaxis: is the trend still going up?

Luciana Kase Tanno,
Marco Caminati,
Guillaume Pouessel
et al.

Abstract: Purpose of review To understand the current global scale of anaphylaxis and identify possible strategies to increase the accuracy of epidemiological data. Recent findings Anaphylaxis mortality and morbidity statistics may gain new perspectives with the global implementation of the ICD-11. Improving the quality of epidemiological data related to anaphylaxis should clarify some areas of uncertainty about risk factors, leading to better targeting of strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…There are differences in prevalence and causes throughout the world probably due to distinct environmental factors which might act differently to affect risk of different types of allergies according to genetic predisposition in diverse areas of the globe and that would account for the rise in the prevalence more rapidly than expected (table I) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Data from the European anaphylaxis registry revealed that over one-quarter of cases (25%) occurred in patients under 18 years of age (14). Although the fatality rate attributable to anaphylaxis remains low (15), the frequency of hospitalization for food and drug-induced anaphylaxis has been increasing in recent years (7,16,17).…”
Section: Epidemiologymentioning
confidence: 99%
“…There are differences in prevalence and causes throughout the world probably due to distinct environmental factors which might act differently to affect risk of different types of allergies according to genetic predisposition in diverse areas of the globe and that would account for the rise in the prevalence more rapidly than expected (table I) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Data from the European anaphylaxis registry revealed that over one-quarter of cases (25%) occurred in patients under 18 years of age (14). Although the fatality rate attributable to anaphylaxis remains low (15), the frequency of hospitalization for food and drug-induced anaphylaxis has been increasing in recent years (7,16,17).…”
Section: Epidemiologymentioning
confidence: 99%
“…A CID-11 veio para corrigir essa falha e teve sua entrada oficial na prática médica em janeiro de 2022. Nela, anafilaxia faz parte do capítulo 4, doenças do sistema imune, facilitando estudos epidemiológicos futuros (WATANABE AS, et al, 2021;TANNO LK, et al, 2023). Apesar de todas estas limitações, na última atualização do Practice Parameter da American Academy of Allergy, Asthma and Immunology/American College of Allergy, Asthma, and Immunology (AAAAI) inferiu-se que a prevalência global da anafilaxia seja de 1,6% a 5,1%, com média de incidência de 50 a 112 episódios por 100.000 pessoas/ano (SHAKER MS, et al, 2020).…”
Section: Introductionunclassified